Rootstocks in developing rustic grapevine in two counties in West of Paraná State, Brazil - Villa, Fabíola; Dall’Oglio, Paulo Antonio; Potrich, Celio; Fogaça, Luciana Alves (Scientia Agraria Paranaensis, 2019)
The vine, when studied in different places and years, allow extensive conclusion on cultural adaptation in a specific region. The objective of this research was to evaluate two rootstocks and three cultivars of rustic grapes under bench grafting at Toledo and Ouro Verde do Oeste (Paraná State, Brazil). Both researches were conducted in a private property, evaluating forming and plant development and of this plants in field. Bench grafting was used for plant forming, by saddle graft. After 90 days grafting root percentage and graft union were evaluated. Then, plants were conducted in field and after 15 days the average sprouting height and number of surviving plants was analyzed. Past 120 days the second phase that consisted of: diameter of horizontal cordon, number of grow plants, number of gems and number of branches than reach the second, and third line of the support system was evaluated. The experiment design was of randomized blocks with factorial arrangement 2x3x2. When the arrangement wasn’t significant for triple and double interaction, each experiment was analyzed alone in factorial arrangement 2x3. All parameters did not show influence concerning local. In the first phase only height of sprouting was significantly at Ouro Verde do Oeste. The IAC-766 Campinas rootstock was better than 420-A to Bordô variety. In the second phase, the IAC-766 Campinas rootstock was more vigorous than 420-A to form a vineyard. Both rootstocks and cultivars are indicated to both counties.